Will the sulphur polypore (laetiporus sulphureus) become a new functional food? - Patocka, Jiri (Global Journal of Medical and Clinical Case Reports, 2019)
Mushrooms are a rich source of chemical compounds. Such a mushroom is also polypore laetiporus sulphureus, in which a large number of bioactive substances with cytotoxic, antimicrobial, anticancer, anti-inflammatory, hypoglycemic, and antioxidant activity have been found. This short review summarizes the results of the most important chemical and biological studies of the fruiting bodies and the mycelial cultures of L. sulphureus. Since the ingredients of this edible mushroom have beneficial effects on human health, it could become a functional food.